Acute kidney injury after in-hospital cardiac arrest in a predominant internal medicine and cardiology patient population: incidence, risk factors, and impact on survival. Issue 1 (1st January 2021) - Patyna, Sammy; Riekert, Kirsten; Buettner, Stefan; Wagner, Anna; Volk, Johannes; Weiler, Helge; Erath-Honold, Julia W.; Geiger, Helmut; Fichtlscherer, Stephan; Honold, Jörg
Abstract: Introduction: Prognosis of survivors from cardiac arrest is generally poor. Acute kidney injury (AKI) is a common finding in these patients. In general, AKI is well characterized as a marker of adverse outcome. In-hospital cardiac arrest (IHCA) represents a special subset of cardiac arrest scenarios with differential predisposing factors and courses after the event, compared to out-of-hospital resuscitations. Data about AKI in survivors after in-hospital cardiac arrest are scarce. Methods: In this study, we retrospectively analyzed patients after IHCA for incidence and risk factors of AKI and its prognostic impact on mortality. For inclusion in the analysis, patients had to survive at least 48 h after IHCA. Results: A total of 238 IHCA events with successful resuscitation and survival beyond 48 h after the initial event were recorded. Of those, 89.9% were patients of internal medicine, and 10.1% of patients from surgery, neurology or other departments. In 120/238 patients (50.4%), AKI was diagnosed. In 28 patients (23.3%), transient or permanent renal replacement therapy had to be initiated. Male gender, preexisting chronic kidney disease and a non-shockable first ECG rhythm during resuscitation were significantly associated with a higher incidence of AKI in IHCA-survivors. In-hospital mortality in survivors from IHCA without AKI was 29.7%, and 60.8% in patients after IHCA who developed AKI ( p < 0.01 between groups). By multivariate analysis, AKI after IHCA persisted as an independent predictor of in-hospital mortality (HR 3.7 (95% CI 2.14–6.33, p ≤ 0.01)). Conclusion: In this cohort of survivors from IHCA, AKI is a frequent finding, with adverse impact on outcome. Therefore, therapeutic strategies to prevent AKI in post-IHCA patients are warranted.